QUALIDADE DE MUDAS DE Coffea canephora: INFLUÊNCIA DO GENÓTIPO, AUXINA E ÉPOCAS DE COLETA DE ESTACA - Chisté, Hérica (2021)
The genetic variability between clones, the season in which the cuttings are collected and the low concentration of endogenous auxin are determining factors for the rooting and quality of conilon coffee seedlings. In this context, the objective was to evaluate the interaction between different concentrations of auxin on the quality of seedlings of five genotypes of conilon coffee collected in summer and winter. The experiment was carried out in a nursery, located at the Experimental Farm of Linhares - ES, between the months of June to November and December to May, winter and summer respectively. The experiment was carried out in a randomized block design in a split plot scheme with four replications of 27 plants, with 14 useful plants in the plot, totaling 108 seedlings per treatment. The plot consisted of five genotypes (A1, LB1, 143, 02 and 748) and indole-3-butyric acid concentrations (0, 500, 1000, 1500 and 2000 mg Lିଵ) and the sub plot constituted by two seasons of cuttings collection (summer and winter). In the R software, correlation was performed using the Pearson method, considering the p-value at a significance level of 0.05 and the creation of the correlation matrix in the Corrplot package. Analysis of variance was performed using the Sisvar statistical program, and when significant, the means were compared using the Scott Knott test at 5% probability. Quantitative regression analyzes were performed to obtain the adjustment equations of the mathematical models. The quality of conilon coffee seedlings is influenced by the time of cuttings collection, by the genotype and by the dose of IBA. Cuttings collected in winter have a lower capacity for shoot formation and AIB promoted an improvement in the performance of less vigorous genotypes. The formation of the aerial part of seedlings of genotype 748 is inhibited by 72% in cuttings collected in winter, and at the point of greatest efficiency at the dose of 726 mg L^(-1) of IBA promotes an increase of 29.40% in length. Of the stem. The seedlings of genotype 143 have reduced development of the shoot genotype and the season has no influence, however, the AIB promoted an improvement in the performance in cuttings collected in the summer with the highest efficiency point at the dose 959 mg Lିଵ). The genotypes A1, 02 and LB1 had very similar responses for both the time of collection of cuttings and the doses of IBA. No differences were detected in the length of the longest root of the conilon coffee genotypes as a function of IBA doses applied, with mean values of 19.75 cm, concerning MSR, the changes as a function of IBA doses were not sufficient for statistical significance. It is concluded that the genotype and the time of collection of the cuttings are the most determining factors in the quality of the seedlings of the conilon coffee tree. Cuttings collected in winter have a lower capacity for aerial part formation. AIB promotes improvement in the growth of less vigorous genotypes.